2016
DOI: 10.1021/acs.jpcc.6b06661
|View full text |Cite
|
Sign up to set email alerts
|

Self-Supported Construction of Three-Dimensional MoS2 Hierarchical Nanospheres with Tunable High-Performance Microwave Absorption in Broadband

Abstract: The three-dimensional (3D) MoS2 hierarchical nanospheres which assembled spontaneously by two-dimensional (2D) lamina have been successfully designed and fabricated in large scale via a simple hydrothermal process. Subsequently, the electromagnetic wave absorption properties of hierarchical MoS2 nanospheres compounded with polyvinylidene fluoride (PVDF) were investigated in a broad frequency range of 2–40 GHz. The results indicated that the MoS2/PVDF nanocomposites possess adjustable and enhanced wave absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(78 citation statements)
references
References 51 publications
5
68
0
Order By: Relevance
“…Supporting Information Figure S2(a,b) exposes reflection losses with various thicknesses and simulation of matching thicknesses, respectively, for the g‐C 3 N 4 /PMMA, CuS/PMMA, and g‐C 3 N 4 /CuS/PMMA nanocomposites along the X‐ and ku‐band frequency. The results exhibit that the maximum reflection loss was blue shifted when the absorber thickness was diminished, correlated by the quarter wavelength mechanism calculated by tm=nc4||normalεr||normalμrfm equation where n , t m , and f m are the odd number, matching thickness, and frequency . According to this theory, when the thickness of the microwave‐absorbing sample was an odd numeral coefficient of λ/4 of the incident waves, the reflected waves of the interfaces having 180° out of phase with the input waves act as destroyer reversal waves .…”
Section: Resultsmentioning
confidence: 67%
“…Supporting Information Figure S2(a,b) exposes reflection losses with various thicknesses and simulation of matching thicknesses, respectively, for the g‐C 3 N 4 /PMMA, CuS/PMMA, and g‐C 3 N 4 /CuS/PMMA nanocomposites along the X‐ and ku‐band frequency. The results exhibit that the maximum reflection loss was blue shifted when the absorber thickness was diminished, correlated by the quarter wavelength mechanism calculated by tm=nc4||normalεr||normalμrfm equation where n , t m , and f m are the odd number, matching thickness, and frequency . According to this theory, when the thickness of the microwave‐absorbing sample was an odd numeral coefficient of λ/4 of the incident waves, the reflected waves of the interfaces having 180° out of phase with the input waves act as destroyer reversal waves .…”
Section: Resultsmentioning
confidence: 67%
“…As shown by the spectra, the maximum reflection loss of microwave absorption was shifted to the higher frequency when the absorber thickness was diminished. This was confirmed by the match frequency fnormalmtrue|μnormalrtrue|true|ϵnormalrtrue|=nc4tnormalm equation where t m and f m are the matching thickness and frequency, known as quarter wave length mechanism …”
Section: Resultsmentioning
confidence: 75%
“…The spectra illustrated more resonance peaks within the PVDF polymeric matrix, originated from dipole interactions between the fluorine unpaired electrons and the surface of nanoparticles. The high electronegativity of fluorine led to the enhancement of unsaturated states and various polarization relaxation times on the surface of nanoparticles, desirable for the microwave attenuation defined by Debye relaxation theory . More unsaturated states leading to the more electrons hopping are desirable for the Maxwell–Wagner effect and microwave absorption properties .…”
Section: Resultsmentioning
confidence: 99%
“…studied a self‐supported construction of three‐dimensional MoS 2 hierarchical nanospheres. This spherical MoS 2 also has good electromagnetic wave absorption performance that the reflection loss can reach −26.11 dB at a thickness of 2.5 mm when the loading amount is 25 wt % . A number of studies have shown that the study of MoS 2 , a material with high dielectric properties, is the right direction.…”
Section: Introductionmentioning
confidence: 97%